Obstacles of the Application of E-Learning Systems as Viewed by Secondary School Teachers at Al-Kurah District - El-Hersh, Ayed; Muflih, Mohammed; Aldhoon, Mamoun (Jordan Journal of Educational Sciences, 2010)
This study aimed at investigating the obstacles that hinder the application of the e-learning system as viewed by secondary stage teachers at Al-Kurah district. A sample consisting of 47 male and 58 female teachers was randomly chosen during the first semester of the academic year 2008/2009. The results of the study indicated that teacher-related obstacles ranked first, followed by administrationrelated obstacles, then infrastructure and equipment-relate obstacles and finally student-related obstacles. The results also indicated that there were statistically significant differences attributed to gender in favor of males in the domain of the obstacles related to infrastructure and basic equipment. The results showed significant statistical differences attributed to academic qualifications in student-related obstacles in favor of teachers with a master’s degree. However, no statistically significant differences were revealed due to the effect of training courses in all study fields. The researchers recommended that the training courses held by the Ministry of Education be evaluated and the infrastructure and its equipment be improved.